Students’ Perception toward the Use of Wayground Flash Card Feature in Learning Narrative Text - Nagata Zamzami; Sherly Novalita Yappy; M. Khusni Mubarok Khusni (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research aims to investigate students’ perceptions and motivation toward the use of Wayground Flash Card in learning English narrative texts. The study employed a quantitative descriptive design focusing on students’ responses without manipulating variables. The participants were secondary school students who had used the Wayground Flash Card feature during English learning activities. Data were collected through online questionnaires distributed via Google Form, which consisted of two main instruments: a perception questionnaire (usability, engagement, usefulness, and enjoyment) and a motivation questionnaire (intrinsic, extrinsic, self-efficacy, engagement, and learning commitment). Each item was measured using a five-point Likert scale. The results showed that students’ overall perception of Wayground Flash Card was positive, with an average mean of 3.97, indicating that students considered the platform useful and enjoyable for learning narrative texts. Among the perception dimensions, usability (4.03) and enjoyment (4.04) received the highest mean scores, reflecting that student found the flash card easy to use and engaging. Meanwhile, motivation analysis revealed an overall positive category, with engagement (4.04) and intrinsic motivation (3.97) emerging as the strongest factors influencing students’ enthusiasm in learning English. These results suggest that Wayground Flash Card effectively supports students’ active involvement and fosters a positive attitude toward English learning. In this study confirms that interactive digital media can enhance learners’ motivation and confidence through autonomy, competence, and enjoyment. The findings also support previous studies indicating that game-based and visual learning media increase learners’ engagement and satisfaction. Therefore, Wayground Flash Card can be considered an innovative and effective tool to improve students’ motivation and learning experience in narrative text writing and comprehension.